PENGARUH PEMASANGAN BALIHO TERHADAP KEPUTUSAN MEMILIH CALON ANGGOTA LEGISLATIF DI KABUPATEN OGAN KOMERING ULU - Safaruddin; Netari Mulyawati; Hema Malini (Pojok Publisher, 2025)
Legislative members are an important element for society in national life, because the people's representative council is a formal state institution as a mainstay and hope for the community. For that, they need legislative members who are always committed to the welfare of the community by improving good cooperation, building strong synergy, and carrying out tasks according to their respective fields, then responsive to input and criticism in carrying out the people's mandate. Generally, they serve for five years, and/or follow the applicable political mechanisms and policies. Because of this, the community will seek information and recognize the legislative candidates they will choose. Prospective legislative members who choose billboards to introduce themselves with the consideration of saving costs and time because without meeting the community can get to know the prospective legislative members. When associated with the function of billboards, many phenomena of destruction and neglect are found by the community. In order to obtain legislative members who are in accordance with what is desired, there are several factors that the community may consider before deciding which legislative candidates to choose. This study aims to determine the effect of installing billboards on the community's decision in choosing legislative candidates in Ogan Komering Ulu Regency.